Determinants of capital structure: Evidence from Sidama credit and saving microfinance institution - Alemayehu Taddese (Jurnal Perspektif Pembiayaan dan Pembangunan Daerah, 2021)
Different industry-specific and macro-economic factors influence the capital structure of microfinance institutions (MFI). So, the objective of this study is to identify industry-specific determinants of capital structure with the selected branch of Sidama MFI, Sidama region, Ethiopia. To this end, the researcher employed a quantitative research approach with an explanatory research design where the effect caused by the independent variable on the dependent variable is observed through regression analysis. The secondary data were collected from Sidama MFIs consolidated and audited financial statements from 2009 to 2019 G.C. Then, both descriptive and inferential statistical analysis has been done. The researcher employed a regression analysis model to identify the effect of five explanatory variables on capital structure measured through debt to equity ratio. Thus, the result of regression analysis showed that out of five independent variables incorporated in the model, all five variables such as growth (negative), profitability (positive), firm size (positive), earning volatility (positive), and asset tangibility (positive) and statistically significant respectively. This study recommends that the microfinance institutions at all company levels improve debt capacity in proportion to asset tangibility more than the current status.